STUDI ETNOBOTANI TIGA PASAR TRADISIONAL DI KABUPATEN TABANAN BALI - Wawan Sujarwo; I Nyoman Lugrayasa; Farid Kuswantoro (BERITA BIOLOGI, 2018)
The trade process makes traditional market able to become a pool of traditional knowledge for various local wisdoms that develop in the local community, including the use of plants. This study aims to document the traditional uses of plant species traded in three traditional markets in Tabanan regency. Data collection was carried out by semi-structured interview toward 64 traders of Baturiti, Marga, and Tabanan traditional markets, respectively. Data analysis was performed quantitatively by calculating the use value index, and some ecological indices, such as diversity index, margalef index, pielou index, sørensen index, cluster analysis, and principal component analysis. Qualitative analysis was also used to tabulate and presented the data into tables and figures. The study documented 52 plant species belonging to 48 genera and 30 families. Herbs are the most widely used habitus, and Zingiberaceae is the most widely used plant family. The most widely used use-category is condiments, and Cocos nucifera is a plant species with the highest use-value. The study also showed a highly plant diversity, which is traded in each market, with slightly different similarities. Cluster analysis and PCA showed that there is a little difference in plants species traded in three traditional markets. Differences in altitude may affect the diversity of plant species traded, including the buyer's preference (community).